1996
DOI: 10.1063/1.116246
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, friction, and wear characteristics of the as-deposited and carbon ion-implanted diamond films

Abstract: The microstructure, friction and wear characteristics of the as-deposited and carbon ion (160 keV, 6.7×1017 ions/cm2) implanted polycrystalline diamond films grown by plasma-enhanced chemical vapor deposition were studied. Cross sectional transmission electron microscopy revealed the amorphous nature of the ion bombarded film. Raman peaks of the ion-implanted film are found to be consistent with the noncrystalline carbon. The pin-on-disk technique was used to determine the friction and wear characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…However, the friction increased somewhat for each cycle. Miyoshi [12] reduced the friction of CVD-diamond in vacuum from 1 to less than 0.2 by ion-implantation. Once the transformed surface layer was worn away, the friction returned to 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, the friction increased somewhat for each cycle. Miyoshi [12] reduced the friction of CVD-diamond in vacuum from 1 to less than 0.2 by ion-implantation. Once the transformed surface layer was worn away, the friction returned to 1.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] . One of the main obstacles to many potential diamond applications is the roughness of the as-deposited films.…”
mentioning
confidence: 99%
“…It was reported that carbon materials such as diamond, DLC and related materials show excellent tribological properties under ambient conditions, however, under vacuum condition like space, they change drastically to be opposite situation. Miyoshi et al reported that friction properties of diamond films under vacuum showed very high values compared with those in air [18,19]. In the case of vacuum condition, dangling carbon bonds on the surface of DLC formed during friction, would react with opposing specimen to give high friction coefficient, whereas in air they would react with water, oxygen and so on.…”
Section: Resultsmentioning
confidence: 96%